2017
DOI: 10.1093/cid/cix623
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response to Malaria During Pregnancy Is Associated With Pregnancy Loss and Preterm Delivery

Abstract: NCT01168271.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 35 publications
2
52
0
2
Order By: Relevance
“…A study by Choi and colleagues (Choi et al, 2016) showed that maternal immune activation increases maternal IL-17a levels, which induces an autism spectrum-like phenotype and brain development abnormalities in offsprings. Other studies have also shown a correlation between poor pregnancy outcomes and the concentrations of systemic cytokines, including TNF-α, IFNγ, and IL-10 in women with malaria (Fried et al, 2017). Abnormally elevated levels of TNF-α in the maternal peripheral blood can be toxic to early embryo development, induces preterm labor in non-human primate models, and mediates fetal demise in mouse models of LPS and poly(I:C)-induced fetal resorption (Yockey et al, 2018).…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
“…A study by Choi and colleagues (Choi et al, 2016) showed that maternal immune activation increases maternal IL-17a levels, which induces an autism spectrum-like phenotype and brain development abnormalities in offsprings. Other studies have also shown a correlation between poor pregnancy outcomes and the concentrations of systemic cytokines, including TNF-α, IFNγ, and IL-10 in women with malaria (Fried et al, 2017). Abnormally elevated levels of TNF-α in the maternal peripheral blood can be toxic to early embryo development, induces preterm labor in non-human primate models, and mediates fetal demise in mouse models of LPS and poly(I:C)-induced fetal resorption (Yockey et al, 2018).…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
“…14,29 The high level of TNF-α during early pregnancy is associated with defects in early embryo development 30 pregnancy-related complications upon malaria infection. 31 A recent systematic review identified increased level of C-reactive protein (CRP) in a majority of COVID-19 positive pregnant women. 20 Taken together, the cytokine storm (pro-inflammatory cytokines) induced by SARS-CoV-2 might place pregnant women at greater risk by causing an increased pro-inflammatory state with the potential to impact fetal brain development; thus, increasing the risk for autism, mental health disorders or schizophrenia.…”
Section: Immunology Of Covid-19 In Pregnancymentioning
confidence: 99%
“…5,52 In women with PM, levels of cytokines and chemokines including CXCL9, IFNγ, IL-10, and IL-1β have been associated with poor pregnancy outcomes including fetal loss, low birthweight, and preterm delivery. 53 It is likely that transfer of immune-modulating factors into the fetal circulation may have additional, currently unknown, influences on fetal immune development.…”
Section: Mal Aria Anti G En E Xp Osure I N Uteromentioning
confidence: 99%